2021
DOI: 10.1007/s00464-021-08384-3
|View full text |Cite
|
Sign up to set email alerts
|

Transanal total mesorectal excision: short- and long-term results of the first hundred cases of a certified colorectal cancer center in Germany

Abstract: Background Since 2010, laparoscopic transanal total mesorectal excision (TaTME) has been increasingly used for low and very low rectal cancer. It is supposed to improve visibility and access to the dissection planes in the pelvis. This study reports on short- and long-term outcomes of the first 100 consecutive patients treated with TaTME in a certified German colorectal cancer center. Patients and methods Data were derived from digital patient files and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…According to the Chinese CTRC database, the reported data from 2022 showed a postoperative overall complication rate of 15.4% for TaTME, which did not show a significant difference compared to traditional laparoscopic TME (13). In a study including 100 TaTME patients, the postoperative complication rate was 32% (14). Similarly, Caycedo-Marulanda et al found a postoperative complication rate of 34% in their study (15).…”
Section: Discussionmentioning
confidence: 80%
“…According to the Chinese CTRC database, the reported data from 2022 showed a postoperative overall complication rate of 15.4% for TaTME, which did not show a significant difference compared to traditional laparoscopic TME (13). In a study including 100 TaTME patients, the postoperative complication rate was 32% (14). Similarly, Caycedo-Marulanda et al found a postoperative complication rate of 34% in their study (15).…”
Section: Discussionmentioning
confidence: 80%
“…After the two worrisome publications, further studies looked even harder at the issue. Fortunately, elevated local recurrence rates were not observed in recent studies, such as the case series published by Simo and Volkel [ 10 , 37 ], the retrospective multicenter study published by Roodbeen [ 38 ], the comparative studies published by Munini and Zeng [ 34 , 35 ], the surveys published by the national database of Denmark and the international taTME registry [ 39 , 40 ], and a new meta-analysis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the two worrisome publications, further studies looked even harder at the issue. Fortunately, elevated local recurrence rates were not observed in recent studies, such as the case series published by Simo and Volkel [10,34], the retrospective multicenter study published by Roodbeen [35], the comparative studies published by Munini and Zeng [31,32], the surveys published by the national database of Denmark and the international taTME registry [36,37], and a new metaanalysis [33].…”
Section: Discussionmentioning
confidence: 99%